2021
DOI: 10.1001/jamanetworkopen.2021.1312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Posttraumatic Headache Phenotype and Recovery Time After Youth Concussion

Abstract: IMPORTANCE The Four Corners Youth Consortium was created to fill the gap in our understanding of youth concussion. This study is the first analysis of posttraumatic headache (PTH) phenotype and prognosis in this cohort of concussed youth. OBJECTIVE To describe the characteristics of youth with PTH and determine whether the PTH phenotype is associated with outcome. DESIGN, SETTING, AND PARTICIPANTS This cohort study examined outcomes from patients in a multi-institutional registry of traumatic brain injury (TBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 27 publications
1
33
3
Order By: Relevance
“…A predisposition to migraine appears to act as a catalyst for PTH development, 48 and some cases of PTH may be the abrupt onset of trauma‐triggered migraine 11 . A recent prospective multicenter cohort study demonstrated that those reporting migrainous headache <8 weeks post‐mTBI were more likely to have a prolonged recovery, and were more likely to be prescribed preventative migraine medication 9 . The authors proposed that migraine phenotype may represent a target for early intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A predisposition to migraine appears to act as a catalyst for PTH development, 48 and some cases of PTH may be the abrupt onset of trauma‐triggered migraine 11 . A recent prospective multicenter cohort study demonstrated that those reporting migrainous headache <8 weeks post‐mTBI were more likely to have a prolonged recovery, and were more likely to be prescribed preventative migraine medication 9 . The authors proposed that migraine phenotype may represent a target for early intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work in children suggests that PTH with migrainous features 5‐9 or a personal or family history of migraine is associated with prolonged recovery 5,6 . The PTH “migraine phenotype” may represent a subset of patients who would benefit from more directed headache management 9 . This is of particular interest in the pediatric population due to the high incidence of migraine in the teenage years and early twenties 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Activation of trigeminal nociceptive pathways has been extensively studied in migraine pathogenesis, and may help explain why there is symptom overlap between migraine and concussion 26,27,39 . Indeed, multiple studies have proposed a migrainous concussion phenotype that has been associated with high symptom burden and prolonged recovery [40][41][42][43][44] . The brain predominant group in our study reported elevation of headache, and light and sound sensitivity, which are cardinal features of migraine 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by the Four Corners Youth Consortium, PTH with a migraine phenotype strongly predicted persistent headache at 3- and 6-months post injury, compared to PTH with a non-migraine phenotype. Although female gender has long been considered a risk factor for prolonged recovery after concussion, this cohort demonstrated that the discrepancy in persistent PTH by gender was explained by a higher likelihood of migraine phenotype in girls [ 9 ].…”
Section: Acute Pth Treatment Modelsmentioning
confidence: 99%
“…Current insurance requirements make targeted CGRP intervention with antibodies and gepants difficult in acute PTH. However, for patients at a high risk of developing persistent symptoms based on clinical risk scores, and perhaps, given the work of Kamins et al [ 9 ], those who have PTH with a migraine phenotype, urgent efficacy studies are needed. In their absence, the author has found that employing corticosteroids, NSAIDs, or long lasting triptans like frovatriptan for a 5-7 day course may be effective to significantly diminish symptoms and shorten the acute symptom course after concussion.…”
Section: Acute Pth Treatment Modelsmentioning
confidence: 99%